A case of atypical band shaped keratopathy following intravitreal silicone oil injection in an aphakic eye - Nischala Balakrishna; Seema Channabasappa (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Introduction: Silicon oil or polydimethylsiloxane fluid is used in complicated retinal detachment surgeries. Although it displays an array of side effects like progressive vascularisation, silicon granules in corneal stroma and corneal decompensation, the lesser known band shaped keratopathy is visually endangering and requires a new management protocol, as was seen in our case. Case: A 15-year-old girl with vision 6/60 in both eyes diagnosed with bilateral congenital cataract and retinal detachment underwent microincision vitrectomy, lensectomy along with perfluorocarbon and intravitreal silicon oil injection in the right eye under general anaesthesia. Calcific band shaped keratopathy was seen after 8 months which began as fine dust like deposits coalescing to form a horizontal band. A neutral, autoclaved solution of 0.5% EDTA chelating agent was spread over the cornea and deposits scraped under aseptic precautions after removing the superficial epithelium. A bandage contact lens was placed to enable healing. Discussion: Calcific band shaped keratopathy with a large silicon oil bubble in anterior chamber commonly seen in aphakics. Calcium salts deposit in the superficial stroma and Bowman's layer due to a lower corneal metabolic rate resulting in less metabolite production. The carbon dioxide evaporation remains unchanged causing increased pH in superficial layers causing precipitation. Conclusion: Calcium hydroxyapatite deposition on the cornea is a rare complication of intravitreal silicon oil injection. Aphakics present with this side effect as a result of permanent contact of silicon oil with the corneal endothelium. These side effects must be noticed in order to prevent impending visual decompensation.